Prior incarceration, restrictive housing, and posttraumatic stress disorder symptoms in a community sample of persons who use drugs - James A. Hammock; Teresa López-Castro; Aaron D. Fox (BMC, 2024)
Abstract Background Criminalization of drugs in the United States (US) has extensive consequences for people who use drugs (PWUD). Incarceration and substance use overlap with 65% of the US prison population meeting substance use disorder (SUD) criteria. Exposure to the criminal-legal system negatively impacts the health of PWUD. PTSD is commonly comorbid with SUDs, and exposure to restrictive housing (RH) during incarceration may worsen mental health. Because PWUD are disproportionately incarcerated, experiences occurring during incarceration, such as RH, may contribute to the development or exacerbation of PTSD and SUDs. This study of PWUD investigated prior criminal-legal system exposure and its association with PTSD symptoms in community-dwelling PWUD. Methods This cross-sectional study recruited PWUD from syringe service programs (SSP). Inclusion criteria were: age 18+, current or past opioid use disorder, and SSP enrollment. Data collected included: sociodemographics; incarceration, substance use, SUD treatment history, and PTSD assessments (Life Events Checklist for DSM-5 and the PTSD Checklist for DSM-5). Bivariate testing and multivariate logistic regression analyses, with probable PTSD as the dependent variable and a three-level variable for criminal legal history as the independent variable, were conducted to determine whether incarceration and RH were associated with probable PTSD. Results Of 139 participants, 78% had an incarceration history with 57% of these having a history of RH. 57% of participants screened positive for probable PTSD, and physical assault was the most common traumatic exposure. Any history of incarceration was not associated with probable PTSD diagnosis; however, in multivariate testing, adjusting for age, sex, and substance use, a history of RH (adjusted odds ratio [aOR]: 3.76, 95% CI 1.27-11.11) was significantly associated with probable PTSD. Conclusions RH and PTSD were both exceptionally common in a sample of SSP participants. RH can be detrimental to physical and mental health. Clinicians and policy makers may not consider incarceration as a traumatic experience for PWUD; however, our data suggest that among highly marginalized PWUD, prior exposure to incarceration and RH may add an additional burden to their daily struggles, namely PTSD.